Advances in Spatial and Temporal Databases 14th International Symposium, SSTD 2015, Hong Kong, China, August 26-28, 2015. Proceedings - Claramunt, Christophe; Schneider, Markus; Wong, Raymond Chi-Wing.; Xiong, Li.; Loh, Woong-Kee.; Shahabi, Cyrus; Li, Ki-Joune.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 14th International Symposium on Spatial and Temporal Databases, SSTD 2015, held in Hong Kong, China, in August 2015. The 24 revised full papers together with 8 demos presented were carefully reviewed and selected from 64 submissions. The conference program has the scope on following subjects: reachability query and path query, reverse query and indexing, navigation and routing, trajectory analysis, spatio-temporal approaches, privacy and matching, similarity search and pattern, keyword and pattern.
Reachability Query and Path Query -- RICC: Fast Reachability Query Processing on Large Spatiotemporal Datasets -- COLD. Revisiting Hub Labels on the database for large-scale graphs -- ParetoPrep: Efficient Lower Bounds for Path Skylines and Fast Path Computation -- Reverse Query and Indexing -- Relaxed Reverse Nearest Neighbors Queries -- Influence-aware Predictive Density Queries Under Road-network Constraints -- Approximate UV computation based on space decomposition -- Navigation and Routing -- Towards Fast and Accurate Solutions to Vehicle Routing in a Large-Scale and Dynamic Environment -- Oriented Online Route Recommendation for Spatial Crowdsourcing Task Workers -- Knowledge-Enriched Route Computation -- Trajectory Analysis -- Efficient Point-based Trajectory Search -- Visibility Color Map for a Fixed or Moving Target in Spatial Databases -- Speed Partitioning for Indexing Moving Objects -- Spatio-temporal Approaches Using Lowly Correlated Time Series to Recover Missing Values in Time Series: a Comparison between SVD and CD -- Minimal Spatio-Temporal Database Repairs -- A Spatio-temporally Opportunistic Approach to Best-start-time Lagrangian Shortest Paths -- Session 6: Privacy and Matching Combining Differential Privacy and PIR for Efficient Strong Location Privacy -- Privacy-Preserving Detection of Anomalous Phenomena in Crowdsourced Environmental Sensing -- Efficient Top-k Subscription Matching for Location-Aware Publish/Subscribe -- Similarity Search and Pattern Spatiotemporal Similarity Search in 3D Motion Capture Gesture Streams -- A Progressive Approach for Similarity Search on Matrix -- Discovering Non-compliant Window Co-occurrence Patterns: A Summary of Results -- Keyword and Pattern Maximizing Influence of Spatio-Textual Objects Based on Keyword Selection -- Geo-Social Keyword Search -- RCP Mining: Towards the Summarization of Spatial Co-location Patterns -- Demonstrations -- Pedestrian Flow Analysis System Improving Exhibition Events -- AETAS: a System for Semanticizing Temporal Expressions from Unstructured Contents -- SCHAS: A Visual Evaluation Framework for Mobile Data Analysis of Individual Exposure to Environmental Risk Factors -- Distributed SECONDO: A highly available and scalable system for spatial data processing -- EasyEV: Monitoring and Querying System for Electric Vehicle Fleets Using Smart Car Data -- TwitterViz: Visualizing and Exploring the Twittersphere -- A Trajectory Recommendation System via Optimizing Sensors Utilization in Airborne Systems -- Tourismo: User Preference Driven Touristic (Trip) Search Engine.
Keywords: Artificial intelligence; Database management; Computer science$1 (BMathematics.s; Data mining; Artificial Intelligence; Database Management; Discrete Mathematics in Computer Science; Data Mining and Knowledge Discovery